Peran Pelatihan Pengelolaan Sampah Sebagai Upaya Meningkatkan Motivasi Dalam Mengelola Sampah Mandiri (Studi Kasus di Provinsi Kepulauan Bangka Belitung) - Imam Rosadi (Jurnal Widyaiswara Indonesia, 2020)
This training of waste management is carried out by Environmental Departement of Bangka Belitung Province, in order to improving the quality of human resources in the field of waste through training. Training carried out are related to efforts to increase motivation of community to self to manage of waste. Community awareness to manage of waste independently must be improved because the economic potential of waste is very large. This training provides knowledge to the community in making compost and utilizing used plastics into handicrafts that have economic value. The method used in this training is a participatory approach, with this method the respondents consist of the training participants. Respondents participate directly in interviews, training, dialogue and execution. Through the implementation of this training, it is hoped that it will be able to increase understanding of the world of solid waste to the community and have an influence on increasing people's motivation to manage their waste independently. Keywords: motivation, training, participatory approach and waste.